Diabetes Mellitus Severity and a Switch From Using Lipoprotein Lipase to Adipose‐Derived Fatty Acid Results in a Cardiac Metabolic Signature That Embraces Cell Death. Issue 21 (5th November 2019) - Puri, Karanjit; Lal, Nathaniel; Shang, Rui; Ghosh, Sanjoy; Flibotte, Stephane; Dyer, Roger; Hussein, Bahira; Rodrigues, Brian
Abstract : Background: Fatty acid (FA) provision to the heart is from cardiomyocyte and adipose depots, plus lipoprotein lipase action. We tested how a graded reduction in insulin impacts the source of FA used by cardiomyocytes and the cardiac adaptations required to process these FA. Methods and Results: Rats injected with 55 (D55) or 100 (D100) mg/kg streptozotocin were terminated after 4 days. Although D55 and D100 were equally hyperglycemic, D100 showed markedly lower pancreatic and plasma insulin and loss of lipoprotein lipase, which in D55 hearts had expanded. There was minimal change in plasma FA in D55. However, D100 exhibited a 2‐ to 3‐fold increase in various saturated, monounsaturated, and polyunsaturated FA in the plasma. D100 demonstrated dramatic cardiac transcriptomic changes with 1574 genes differentially expressed compared with only 49 in D55. Augmented mitochondrial and peroxisomal β‐oxidation in D100 was not matched by elevated tricarboxylic acid or oxidative phosphorylation. With increasing FA, although control myocytes responded by augmenting basal respiration, this was minimized in D55 and reversed in D100. Metabolomic profiling identified significant lipid accumulation in D100 hearts, which also exhibited sizeable change in genes related to apoptosis and terminal deoxynucleotidyl transferase dUTP nick‐end labeling–positive cells. Conclusions: With increasing severity of diabetes mellitus, when the diabetic heart is unable to control its own FA supply using lipoprotein lipase, it undergoes dramatic reprogramming that is linked to handling of excess FA that arise from adipose tissue. This transition results in a cardiac metabolic signature that embraces mitochondrial FA overload, oxidative stress, triglyceride storage, and cell death.